English for hospitality training at Warung Pantai Seseh - Putu Chrisma Dewi; Putu Chris Susanto; Ni Luh Christine Prawitha Sari Suyasa (Universitas Muhammadiyah Magelang, 2022)
Beachside restaurant is one of Bali's popular tourism industries right now. One of them is Warung Pantai Seseh, a restaurant and MSME that is located in Seseh Beach, Badung Regency. The primary problem is a lack of English communications skills in the hospitality. To enhance excellent service to tourists, steps to increase English proficiency also are required. Implementation methods used include a pre-test, training, and a post-test which was attended by 11 Warung Pantai Seseh employees. The employees of Warung Pantai Seseh have improved their knowledge and skill in English for hospitality as a result of the community service. Results from the post-test indicate that 81.8% of employees have good English for hospitality skills, with a minimum score of 80.